Research on Multimedia Technology-Assisted College English Grammar Teaching - Xu, Huarui; Yao, Yun (Wireless communications and mobile computing, 2022)
The English Curriculum Standard for Compulsory Education lists the specific requirements for the integration of English discipline and information technology to optimize the presentation of education. For college students’ English teaching, the most appropriate and effective way is to widely apply multimedia courses to English teaching. Using the rich multimedia knowledge of multimedia courses to expand students’ oral English and teaching skills, widen the reading path of reading and writing, multimedia tutoring teaching can concretize and visualize abstract knowledge well, and rich multimedia knowledge can facilitate students’ learning and play an important role in understanding knowledge. This paper focuses on multimedia technology-assisted college English grammar teaching. The multimedia technology is analyzed by using the multimedia data hashing algorithm with semantic fusion. Then, the application of multimedia teaching materials in teaching and traditional teaching methods is experimented. By comparing their learning effects, the author draws a conclusion that multimedia technology has been applied in English grammar teaching to a certain extent, and the present situation of its application is relatively good. Most of them have an encouraging attitude, especially in improving students’ learning attitude and increasing their interest in learning. Due to the limitations of awareness and conditions, the extent and progress of the integration of information technology and disciplines have lagged behind relatively, and there are many difficulties in the application of multimedia course materials; there are certain difficulties in integrating multimedia course materials and English subjects.